Analisis persepsi dan perubahan keputusan pembelian konsumen terhadap gula campuran - Mustaufik Mustaufik; Suliyanto Suliyanto; Refius Pradipta Setyanto; Hidrotunnisa Hidrotunnisa (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Blended sugar/refined brown sugar/cooking sugar is a mixture of coconut and refined crystal sugar (GKR). The lower selling price of mixed sugar than coconut sugar can reduce consumer buying interest in coconut sugar, thereby reducing the welfare of coconut sugar artisans. Therefore, this study needs to examine consumer perceptions and changes in the purchasing intention of mixed sugar in the domestic market. Data collection through questionnaires and interviews with 150 coconut sugar consumer respondents in Banjarnegara, Purbalingga, Banyumas, Cilacap, and Kebumen. The respondent selection technique used purposive random sampling and is proportional based on the population in each district. The study of changes in purchasing decisions (switching intention) for mixed sugar was analyzed using non-parametric statistics using the McNemar Test, a paired-sample 2-sample difference proportion test method.The results of the study showed that consumers perceive coconut sugar to have a good impact on health (91% of respondents), GKR harms health (59% of respondents), mixed sugar harms health (57% of respondents), and are against mixed sugar even though it is cheaper than coconut sugar (66% of respondents). Purchasing decisions show consumers are more willing to buy coconut sugar (60%; 48% unswitched, 12% switched intention) than mixed sugar (40%; 5% unswitched, 35% switched intention). There was a significant change in the purchase decision. As many as 35% of respondents switched intentions and decided to be willing to buy mixed sugar, considering the product's low price.